Análise citogenética de células-tronco derivadas do subendotélio da veia umbilical humana - Duarte, Denise de Medeiros (2009)
Mesenchymal stem cells (MSCs) are known as a population of multi-potential cells able to proliferate and differentiate into multiple mesodermal tissues including bone, cartilage, muscle, ligament, tendon, fat and stroma. Several applications of the study of EC can be emphasized the therapeutic techniques such as guided bone regeneration by implantation of EC in the affected site, without the need for bone grafts, using titanium as a vehicle. The process of cryopreservation is essential for the maintenance of cell cultures, since the cell line is frozen, it can be maintained in liquid nitrogen for an indefinite period and then thawed for therapeutic or experimental purposes. The aim of this study was to isolate a population of MSCs derived from the subendothelium of the umbilical vein human (MSCs-SUVH) to assess cytogenetic analysis by the possibility of appearance of chromosomal changes in two different situations: MSCs-SUVH regarding the process of cryopreservation and MSCs-SUVH grown on the surface of titanium. Flow cytometry analysis revealed that, this cell population was positive for the markers CD29, CD73 and CD90, but there was no expression of hematopoietic lineage markers, such as CD14, CD34 and CD45 and demonstrated capacity for osteogenic differentiation. The chromosomes obtained from the primary culture of MSCs-SUVH were analyzed by GTW banding technique, and results are described as guidelines to ISCN 2005. There was not the emergence of clonal chromosomal changes in the MSCs-SUVH in different situations analyzed. However one of the strings presented a balanced paracentric inversion, probably a cytogenetic constitutional alterations, which was present before and after the experimental situations that the MSCs-SUVH was submitted